Influência do hipoclorito de sódio e da ação de corte na resistência à fadiga de instrumentos endodônticos de níquel-titânio acionados a motor - Renata de Castro Martins (2003)
The present study evaluated the influence of sodium hypochlorite (NaOCl) and of the cutting action on the fatigue resistance of ProFile rotary NiTi endodontic instruments, employed for shaping 10 curved root canals and then tested in fatigue, using a stand for fixation of the hand piece and an carbon steel artificial canal with radius of 4mm andangle of curvature of 45º. The number of cycles to failure was determined in terms of the measured test time and the rotation speed, 250rpm. Eighty new instruments, 20/.06, 30/.04, 25/.04 and 20/.04, were randomly divided into a four Groups, with 20 samples in each Group, (five of each size), in the following conditions: control Group, with 5 non-used instruments of each type; Group 1 with the same amount ofinstruments, which were immersed for 24 hours in a solution of NaOCl 5.25%; Group 2, also with 5 instruments of each type, previously employed for preparing 10 curved canals of extracted teeth using deionized water as irrigant; and Group 3, with the same amount of instruments, after their use in formatting 10 curved canals using NaOCl5.25% as irrigant. The immersion in NaOCl did not affect the surface of the instruments nor their fatigue resistance, whereas the cutting action resulting of their use in formatting curved canals was the critical factor to reduce the number of cycles to failure (Students t test and Kruskal-Wallis p < 0,05)e. It has been observed that the fatigue resistance decreased with the increase in instrument size, in all Groups. The instruments of Group 3 were statistically faster in shaping the root canals than those inGroup 2 (Students t test p< 0,05). There was a tendency of the instruments of Group 3 to show greater fatigue resistance than those of Group 2, although these results were not statistically significant (Students t test and Kruskal-Wallis p > 0,05). The use of NaOCl during shaping of curved root canals reduced the time spent in the instrumentation and this can be an important factor to increase the useful life of theinstruments.